Research of Electromagnetic Parameters of Single-layer Three-phase and Six-phase Chain Windings - Buksnaitis, J. (Elektronika ir Elektrotechnika, 2013)
The research of electromagnetic parameters of single-layer three-phase and six-phase chain windings was accomplished. It was determined that the instantaneous space distributions of rotating magnetomotive force in the three-phase chain winding are asymmetrical in respect of coordinate axes and symmetrical in respect of the origin of these axes. Instantaneous space distributions of rotating magnetomotive force generated by six-phase chain winding, contrary to the three-phase windings, are symmetrical in respect of coordinate axes. After accomplishing harmonic analysis of spatial rotating magnetomotive forces, it was obtained, that odd and even harmonics exist in the harmonic magnetomotive force spectrum generated by three-phase winding, and only odd harmonics in the spectrum generated by six-phase winding. The electromag-netic efficiency factors were calculated for both types of windings, and it was determined that for six-phase winding this factor is 23,7 % higher compared to three-phase winding. Furthermore, it was estimated, that the conditional amplitude of fundamental magnetomotive force harmonic in the analyzed six-phase winding is 2,13 times larger compared to the same amplitude value in the analogous three-phase winding. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5644